Towards hepatitis B elimination in Ghana: vaccination coverage and its predictors among informal sector workers in Kejetia, Kumasi, Ghana - Michael Agyemang Obeng; Daniel Kobina Okwan; Clinton Owusu Boateng; Godfred Yawson Scott; Joshua Kofi Attah; Senam Yawa Nunamey Ahadzie; Nathaniel Darko Antwi; Pius Takyi; De-Graft Kwaku Ofosu Boateng; Augustine Yeboah; Derrick Wedam; Emmanuella Asaamah Ofori; et al. (PLoS ONE, 2026)
Hepatitis B virus (HBV) infection remains major public health concern in Ghana, where prevalence is high despite the availability of an effective vaccine. Informal sector workers represent a large proportion of the national workforce but have limited access to preventive health services. This study assessed hepatitis B vaccination coverage and its predictors among informal sector workers in Kejetia market, Kumasi, Ghana. A cross-sectional analytical study was conducted among 809 market workers selected using stratified random sampling across different occupational groups. Data were collected using structured interviewer-administered questionnaires covering sociodemographic characteristics, HBV awareness and knowledge, and vaccination history. Vaccination uptake was categorized as at least one dose (≥1) and full coverage (≥3 doses). Logistic regression analyses were used to identify predictors of vaccination uptake. Overall, only 137 (16.9%) had completed the three-dose schedule, though 256 (31.6%) of participants reported having received at least one dose of HBV vaccine. While 718 (88.8%) of respondents had heard of HBV infection, 619 (76.5%) reported very little or no knowledge about the disease, and 402 (49.7%) did not know its routes of transmission. Vaccination uptake was significantly higher among those who had received HBV-related health education, 175 (62.7%) compared to those who had not 18 (15.3%, p < 0.001). In the multivariate logistic regression model, ≤ 30 years (aOR = 2.209, 95% CI [1.140–4.282], p = 0.019), secondary education (aOR = 2.426, 95% CI [1.220–4.824], p = 0.012), and tertiary education (aOR = 4.796, 95% CI [2.121–10.845], p < 0.001) were the independent predictors of vaccination status. HBV vaccination coverage among informal sector workers in Kejetia Market is alarmingly low despite high general awareness of the infection. Sociodemographic factors and receipt of HBV-related health education strongly influenced uptake. These findings underscore the urgent need for targeted health education and subsidized vaccination programs tailored to informal sector workers in Ghana to achieve national HBV elimination goals.